Potential Shariah Non-Compliance Practices in E-Bidding: Observation from E-Bidding Platforms in Malaysia - Muhamad Azhari Wahid; Khairil Faizal Khairi; Hamdi Hakeim Mudasir; Azuan Ahmad; Azrul Azlan Iskandar Mirza; Mohd Zakhiri Md Nor; Muhammad Farid Hadhari Mahamed Rusdi (Universiti Sains Islam Malaysia, 2024)
Non-Indexed Publication